Morpheme-based versus word-based morphology - De Guzman, Videa P. (Philippine Journal of Linguistics, 2006)
Several questions have been raised about morphology over the past few decades and various accounts have there by been proposed. Some linguists favor a morpheme-based morphology whereas others argue for a word-based type. Still others contend with neither one. Two of such types - Lexical Morphology and Seamless Morphology - are explored here to determine which better represents the morphological system of any given language. The three aspects of morphology reviewed in each type are inflection, derivation, and compounding. The cases of affixation and reduplication, being prevalent morphological processes in Philippine languages, are also used to test the plausibility of each theory. Furthermore, this paper also makes reference to some language acquisition and psycholinguistic studies that may shed light on the issue.